UiTM panic button using location-based Algorithm / Fatin Munirah Musa - Musa, Fatin Munirah (2015)
Nowadays, almost everyone have smartphone provided with Global Positioning System (GPS) in it. Other than giving direction to a destination needed, it is also can be very helpful when emergency situation happen to the user. This is because when an emergency happen such as an accident, usually, people will become clueless or panic until sometimes they cannot remember the exact location and do not know what action to be made. Besides, there is no time to find numbers from call list and also it is difficult to report emergency especially when panic. So, this project described about the application that will be a helping tool during emergency situation. The application is called UiTM Panic Button Using Location-Based Algorithm. This application basically will help by giving the information of the registered student of UiTM Jasin including the position of them in the form of latitude and longitude to the "Polis Bantuan" with only a button-click application on smartphone. The application will be use Location-Based Service (LBS) which is GPS technology. As a result, UiTM Panic Button Application that can alert ‘Polis Bantuan’ was produced. For usability testing, it shows that 93% of the respondents satisfied with the application. By having this application, it may be able to assist student when facing emergency situation.